Development of a Web-Based Trading Term Application Using Flask Framework at PT. XYZ - Larasati, Sarah; Susetyo, Yeremia A. (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2024)
The use of information technology in data management and collaboration with suppliers has increased efficiency for retail companies such as PT. XYZ. However, some companies still still need help managing data and cooperation agreement documents, which hinders the preparation of reports and has the potential for conflict. This research aims to build a web-based Trading Term application using the Flask framework at PT. XYZ. This application was developed in Python because of its simplicity and diversity of libraries. The waterfall method used in this research includes several stages, including data analysis, software design, system implementation, testing, and application maintenance. The application of the MVC architectural pattern supports fast website development. This research produces a Trading Term Application, to help record and store trade agreement data, thereby increasing efficiency and order in business cooperation. The results of black box testing show that the Trading Term Application developed has passed a series of tests well and has achieved 100% success in the functional tests carried out.